Comparative Study of Main Meteorological Factors Inside and Outside the Forest of Xianweng Mountain National Forest Park. Issue 1 (May 2020) - Ren, Guoli; Yang, Xuewen; Wang, Xue; Zhang, Yaosheng; Li, Shengju; Li, Lan
Abstract: Investigations of meteorological conditions can reveal the dynamics of microclimates in specific forests. Meteorological factors are necessary factors for quantitative observation and research of forest ecosystems. A systematic analysis of the forest boundary and the main meteorological factors outside the forest in Xianweng Mountain National Forest Park can accurately reveal the interaction between the forest and meteorological factors in Xianweng Mountain National Forest Park. Based on the meteorological observation data of the forest of Xianweng Mountain National Forest Park for three consecutive years, and using experimental methods to locate meteorological factors inside and outside the forest, compare meteorological factors such as atmospheric temperature, relative humidity, precipitation and wind speed, and wind direction, and analyze their different characteristics. The results show that the main reason for the difference in temperature and humidity inside and outside the forest is that the canopy absorbs solar radiation and emits long-wave radiation from the ground. The dense canopy also impedes air exchange inside and outside the forest, reducing wind speeds in the woods. Meteorological factors play an important role in guiding the distribution of forests, and have an important impact on the growth of trees in the forest, the development of trees, and the accumulation of tree biomass. A systematic comparative analysis of the main meteorological factors inside and outside the forest of Xianweng Mountain National Forest Park revealed the interaction between the forest and meteorological factors of Xianweng Mountain National Forest Park. According to the meteorological observation data of Xianweng Mountain National Forest Park, in order to make reasonable use of meteorological resources in the future, to develop forests, to protect the balance of natural ecosystems and their healthy development are of great significance.